Progressões e funções: da variação e caracterização das função es do tipo exponencial e logarítmica às técnicas de ajuste de curvas no uso de modelagem matemática - Ferri, Orlando Eduardo da Silva (2014)
This work presents a proposal for teaching exponential and logarithmic functions, preceded by the concept of progressions which allows high school teacher dealing with the concept of exponential and logarithmic function more clear and constructive way for the student. Proposes the construction of knowledge through mathematical modeling developed from the use of built in spreadsheets and dynamic geometry (GeoGebra) environment tables activities, exploring the intuitive ideas of variation and characterization of these real functions from progressions in discrete domain. Presents suggestions for interdisciplinary activities involving estimates by adjusting curves.